Kadar Glukosa Darah Sewaktu pada Pasien Diabetes Melitus Tipe 2 di Puskesmas Siwalima Periode Februari 2021 - Stephanie Sugiharto (Jurnal Health Sains, 2021)
Diabetes mellitus is a metabolic disorder that is heterogeneous and characterized by the presence of hyperglycemia due to impaired insulin secretion, impaired insulin work or both. The prevalence of diabetes mellitus in Indonesia in 2013 was 2.1%. That's higher than in 2007 (1.1%). A total of 31 provinces (93.9%) showed a significant increase in the prevalence of diabetes mellitus. The prevalence of diabetes mellitus in Maluku Province is 0.7%, while based on nakes diagnosis it was found at 0.4%. Prevalence by district is highest in West Southeast Maluku Regency. The percentage of cases of diabetes mellitus that has been served by health workers by district, the lowest in Western Seram and Aru Islands.  The purpose of this study is to find out blood glucose levels when in patients with type 2 diabetes mellitus in the health center siwalima period of February 2021.This study uses descriptive research methods, the study subjects are type 2 diabetes mellitus patients who have blood sugar examination results during and are examined at the general poly Siwalima Health Center in the city of Dobo Aru Maluku Islands in February 2021. Gender, Age, Blood sugar levels at the time, weight, height and waist circumference were recorded from medical records data. There were 17 patients who had type 2 diabetes mellitus, mostly women (52.94%), ages 45–64 years (64.70%), blood sugar levels when the most >180mg / dl (47.05%), overweight body mass index (41.17%), waist circumference above 80 cm in women (66.67%). The conclusion of the study was that DMT2 patients at puskesmas Siwalima Kota Dobo Aru Islands showed most had average blood levelswhen it wasbad.